Benedictine Culture 750-1050 - Lourdaux, W. (Mediaevalia Lovaniensia - Series 1/Studia, 1983)
At the suggestion of the Benedictine, Cistercian and Trappist communities of Belgium, Netherlands and Luxembourg, the 10th International Colloquium (May 19-21, 1980) organized by the Instituut voor Middeleeuwse Studies was devoted to the commemoration of the 15th Centenary of the birth of St. Benedict of Nursia. It was clear to the editors of the present collection of essays that only select aspects of the manifold cultural and economic life of these monastic communities could be presented in a single volume. Nevertheless it was hoped that the reader might intuit the constant evolution and adaptation to altered social circumstances characteristic of the Benedictine communities, and thus participate in the process of discovery shared by members of the Colloquium. To enhance this sense of discovery and to suggest the continuing Benedictine contribution during the following epoch, the editors accepted a final study, which of course extends beyond the strict chronological limits of the volume.